Heart and neurologic disease - Biller, Jose (Handbook of clinical neurology, 2021)
"Cardiac disorders and diseases may often co-occur with, or cause, subsequent neurological disorders. Heart and Neurologic Disease identifies the top cardiac diseases and disorders most likely to have neurological disorders, how they will present, and how they are best treated. It identifies the mechanisms of action explaining why the conditions co-occur, and what clinicians should look for symptom wise, and how risk may be assessed. Coverage includes genetic cardiac disorders, cardiac trauma, surgery, infection, disease, and arrhythmia"--Publisher's description